Augmented Reality Based Learning Media on Geometry Learning Integrated Science Technology Engineering Art Mathematic-Project Based Learning - Dyah, Dyah Susilowati; Syafitri Chani Saputri, Dian; Ratu Perwira Negara, Habib; Rahim, Abdul; Marlina, Marlina; Rizki Aprilian, Faida (Universitas Pendidikan Ganesha, 2025)
Geometry learning, especially on the concept of building space, still faces challenges in delivering abstract material, so students have difficulty in understanding concepts visually and spatially. This study aims to develop learning media for building mathematical geometry on Augmaented Reality (AR) in integrated learning science, technology, engineering, art, mathematic project-based learning and determine the effectiveness in improving student learning outcomes. The research method uses Multimedia Development Life Cycle. The sampling technique used purposive sampling and the test subjects were elementary school students. Data collection instruments used validation sheets and questionnaires. The analysis technique used quantitative descriptive statistical analysis techniques and percentages. The results of Augmaented Reality learning media expert validation are in the very feasible category. Field trials of Augmaented Reality learning media produced were in the very interesting category. The effectiveness test with an N-Gain score of 0.81 shows that Augmaented Reality learning media can improve learning outcomes from before and after using integrated Augmaented Reality learning media-project based learning. The novelty of this research lies in the integration of AR with the STEAM-PjBL learning model in the context of geometry learning, which provides an interactive experience and improves students' understanding of spatial concepts. The broader implications of this research include the potential application of AR in various subjects to improve student engagement and learning outcomes in the digital era.